Indonesian consumer complaint behavior: The role of information seeking, knowledge, purchase behavior, and tendency to talk - Lilik Noor Yuliati; Megawati Simanjuntak (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aimed to determine the effect of information-seeking, knowledge, purchasing behavior, and word-of-mouth on complaint behavior. Design/methodology/approach: This study was conducted in rural and urban areas of 28 provinces in Indonesia. The respondents in this study are consumers who have worked (have income) or are married, aged 17-60 years, and have made consumption decisions independently. The respondents totaled 4200 people, including 2175 people in urban areas and 2025 in rural areas. The Kish Grid method used in social research, especially household surveys, was used to determine respondents. The study was conducted through direct interviews with respondents. Findings: The results showed that purchasing behavior is influenced by consumer knowledge and information seeking. Purchasing behavior also affects WOM. In addition, complaint behavior is influenced by purchasing behavior, consumer knowledge, and WOM. The results show WOM has a significant effect on complaint behavior. Research limitations/implications: Managerial implications for companies providing direct and online complaint services. Managerial implications for the government include providing advertisements related to complaining institutions as complaint services for the public and providing consumer education. The managerial implication for the community is to increase knowledge of consumer rights and consumer protection agencies. Originality/value: This is an original study that explores the factors that directly and indirectly cause the complaint behavior of Indonesian consumers. This study provides benefits for Indonesian consumers to pay more attention to seeking information related to a product/service so that they can increase their knowledge, good purchasing behavior, and courage to WOM so that they have a strong reason to complain.
Keywords: 650; nformation seeking; Knowledge; Purchase behavior; Word-of-mouth; Complaint behavior